2012
DOI: 10.1007/s10815-012-9767-1
|View full text |Cite
|
Sign up to set email alerts
|

Sperm meiotic segregation, aneuploidy and high risk of delivering an affected offspring in carriers of non-Robertsonian translocation t(13;15)

Abstract: Purpose To determine the percentage of unbalanced spermatozoa and an interchromosomal effect in two carriers of balanced translocations t(13;15)(q32;q26) and t(13;15)(q32; p11.2). Methods Sperm nuclei analysis by fluorescent in situ hybridization for detection of percentage of unbalanced spermatozoa and sperm with disomy of chromosomes X, Y, 8, 18, 21 and diploidy. Results The incidence of unbalanced spermatozoa was 50.5 % and 44.6 % in patient 1 (P1) and patient 2 (P2), respectively. Partial disomy of chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…Although numerous chromosome products can be generated through different segregation modes, a prevalence of alternate segregation products was observed in this study, followed by adjacent 1 products. Our results are in agreement with several previous studies of reciprocal translocations, which show an enhanced tendency of homologous centromeres to migrate to opposite poles (Anton et al, 2008;Kasikova et al, 2012;Lledó et al, 2010;Midro et al, 2006;Nishikawa et al, 2008;Yakut et al, 2006). Some studies, however, have reported the frequency of adjacent 2 products to be higher than alternate or adjacent 1 (Escudero et al, 2003).…”
Section: Discussionsupporting
confidence: 93%
“…Although numerous chromosome products can be generated through different segregation modes, a prevalence of alternate segregation products was observed in this study, followed by adjacent 1 products. Our results are in agreement with several previous studies of reciprocal translocations, which show an enhanced tendency of homologous centromeres to migrate to opposite poles (Anton et al, 2008;Kasikova et al, 2012;Lledó et al, 2010;Midro et al, 2006;Nishikawa et al, 2008;Yakut et al, 2006). Some studies, however, have reported the frequency of adjacent 2 products to be higher than alternate or adjacent 1 (Escudero et al, 2003).…”
Section: Discussionsupporting
confidence: 93%
“…In our case, the translocation carried by the father was a re- in translocation carrier's spermatozoa in comparison with the control group (0.11%), stating this is an important finding in regard to ICE (Baccetti et al, 2003). Other than that, two different studies (Kasikova et al, 2012;Vozdova et al, 2012) (Blanco, Egozcue, & Vidal, 2000).…”
Section: Ta B L Esupporting
confidence: 45%
“…Previous papers analyzed ICE with multiple FISH probes to detect whether the copy numbers of sperm or embryo chromosomes had changed. Several studies used multiple FISH to assess the occurrence of ICE in structural rearrangement carriers by analyzing the frequencies of numerical abnormalities in the sperm from rcp carriers [16,17] and from RT carriers [18,19]. Some studies suggested that ICE existed in the sperm from both rcp and RT carriers [20][21][22][23] or were only found in RT carriers [18,19,[24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Others proposed that ICE were not present or negligible [4,29]. Pinar et al investigated cleavage-stage embryos from translocation carriers undergoing PGD, which were biopsied by mFISH for the chromosomes involved in the translocation in addition to chromosomes13, 15,16,17,18,21,22, X, and Y. They found no ICE in embryos derived from Robertsonian and reciprocal translocation carriers [30].…”
Section: Discussionmentioning
confidence: 99%